2018
DOI: 10.1097/psy.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality in Chinese College Students: Associations With Depression and Physical Activity in a Cross-Sectional Study

Abstract: Depression and low levels of PA are associated with lower levels of semen quality, which may have implications for reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…The effects of psychological stress on male reproductive health is an interesting and worthwhile area of study. Our previous studies demonstrated that depression and work-related stress were negatively associated with sperm concentration and total sperm count in Chinese men [19,20], which is consistent with findings from other countries [2,4]. In this study, spermatogenesis impairment was induced by chronic stress in the uCMS rat model.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of psychological stress on male reproductive health is an interesting and worthwhile area of study. Our previous studies demonstrated that depression and work-related stress were negatively associated with sperm concentration and total sperm count in Chinese men [19,20], which is consistent with findings from other countries [2,4]. In this study, spermatogenesis impairment was induced by chronic stress in the uCMS rat model.…”
Section: Discussionsupporting
confidence: 91%
“…To analyze the relationship between depression grade and semen quality, logistic regression model was used after converting the sperm concentration, semen volume, total sperm count, and progressive motility from continuous variable data to binary variables. The "WHO Human Semen Inspection and Processing Laboratory Manual" ( fth edition) was used to determine whether the indicators are quali ed or not [7]. The values of semen quality indicators were directly incorporated into the linear regression model as continuous variable data, and depression symptoms were incorporated into the model as dichotomous variable data [30].…”
Section: Discussionmentioning
confidence: 99%
“…At present, few studies have investigated the association between depressive symptoms and semen quality in the general Chinese population. A recent single center study on Chinese college students showed that, depressive symptoms may be associated with decreased semen concentration and total sperm count [7]. However, the conclusion of this study cannot represent the majority of Chinese men, because the study population is limited to college students and belongs to a single-center study design.…”
Section: Introductionmentioning
confidence: 93%
“…Linear regression and logistic regression analyses were used for the association analysis between anxiety and semen parameters. When using the logistic regression analysis model, four semen parameters (sperm concentration, semen volume, total sperm count and progressive motility) were all divided into two categories: quali ed and unquali ed, according to the "WHO Human Semen Inspection and Processing Laboratory Manual" (2015 fth edition) [35] . The linear regression model directly incorporated the values of semen quality indicators into the regression model according to continuous variable data and anxiety symptoms into the model according to dichotomous variable data [36] .…”
Section: Discussionmentioning
confidence: 99%